Political Islam, Iran, and the Enlightenment: Philosophies of Hope and Despair: By Ali Mirsepassi (New York: Cambridge University Press, 2011. pbk. 241 pages) (American Journal of Islam and Society, 2011)
Political Islam, Iran, and the Enlightenment is Mirsepassi’s latest treatisethat focuses on the Iranian intellectual and political climate. Mirsepassiis concerned to show the German and French intellectual influences of Islamistintellectuals as they search for an appropriate response to modernity.With Iran taken as a case study, Mirsepassi’s discussion is intended to underminethose analyses of Muslim political aspirations which deem theseaspirations to be inherently anti-Western. Comprising an introduction andseven chapters, Mirsepassi’s work speaks to those researchers in a range ofsociopolitical disciplines concerned with coming to grips with intellectualdevelopments in the Muslim world. The book might also interest thoseinterested in understanding the impact of continental philosophy on theMuslim world. Although the emphasis is on Iran, an attempt is made inthe final chapter, especially, to broaden the discussion by dealing with theIndian experience of modernity.According to Mirsepassi, the Muslim understanding of modernity andsecularism was influenced by the specific visions of modern society heldby Kemal Ataturk and the “Shah of Iran” (presumably the ambitious RezaShah). These two figures were in turn influenced by the antireligious fervorof French secularism. The attempt of Muslim intellectuals, therefore, toestablish a correct vision of society was informed by the radical Counter-Enlightenment figures of German and French philosophy. Furthermore,Muslim intellectuals overlooked Western visions of modern society whichwere not antireligious. Political Islam, Iran, and the Enlightenment, therefore,constructs a narrative that leads to examining the experience of British-style secularism in India. Mirsepassi’s fear is that a lack of appreciationof the European heritage of Islamists ‒ who Mirsepassi sees as intellectuallyand politically totalitarian and as representing all Muslims ‒ will leadto the sidelining of two groups from within the Muslim world. These twogroups are the quietist ulama and the reformist intellectuals, the latter ofwhich offer Mirsepassi the hope of an Islamic response to modernity thatis consistent with democratic principles ...